Anxiety levels of 1st and 5th-year dental students in Portugal - Cross-sectional study - Maria Júlia Gonçalves; Luís Proença; Maria Alzira Cavacas (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2024)
Objectives: To evaluate the level of anxiety experienced by 1st and 5th-year dental students in Portugal. Methods: The target population was students from Portuguese universities attending the 1st and 5th years of dental school during the academic year 2022/2023. Data were collected using the previously validated Modified Dental Anxiety Scale, available online on the Google Forms platform between February 2023 and June 2023. Data were statistically analyzed using IBM SPSS Statistics version 29, using descriptive and inferential analysis methods. The Mann-Whitney and Kruskal-Wallis tests were used at a 5% significance level (p<0.05). Results: The sample of 301 students included 146 from the 1st year and 155 from the 5th year, and the majority were Portuguese, female, and in the age groups 17-20 and 21-24. Most of the students had typical levels of anxiety when in the patient's position, although there were differences between years and age groups (p<0.05). Regarding dental specialties, most students feared Oral Surgery and Endodontics. Conclusions: First-year students were more likely to feel anxiety related to dental treatment when in the patient's position. This finding may derive from their lack of clinical experience, which could help students overcome previous bad experiences. The patient's interest and knowledge should make it easier to understand the results of the treatments and why they need to be carried out.